PUMP AS TURBINES (PATS) DESIGN OPTIMIZATION AS A RENEWABLE ENERGY SOURCE ALTERNATIVE - Koswara, Engkos; Rachmat, Asep; Sumirat, Perly (Universitas Muhammadiyah Jakarta, 2021)
One economical alternative to building a small-scale hydroelectric power plant is to use pumps as turbines, often referred to as PATs, which stands for Pump As Turbines. This research was conducted with an experimental method using a factorial experiment 22 After conducting research and data processing, Angle of Entry of Pump As Turbines and impeller tip angles Factors on turbines are equally influential to increase the speed of turning Pump As Turbines (PATs), but the variables the most influential in this study to increase the rotational speed of Pump As Turbines is the entry angle of PATs. Based on data processing to find the most influential variable using the Yates algorithm, if changing the PATs Entry Angle from 45° to 90° there will be an increase in Pump As Turbines rotational speed of 30.1 rpm while changing the impeller tip angles from 40° to 30° can only increase the Pump As Turbines rotational speed by 18.6 rpm. The alternator capacity that can be produced by Pump As Turbines is 100W, based on electrical power testing using a load of incandescent light bulbs. The electric power that can be generated by Pump As Turbines uses test samples at optimum conditions, namely the 90° Angle of Entry and the impeller tip angle 30° at the water pressure from the input pump 0.375 bar (g). The results of loading given using incandescent light bulbs with the power of 5 W, 10 W, 25 W, 40 W, and 100 W, there is the lowest voltage that is 194 V on a light bulb with 100 Watt power with alternator rotational speed of 855.7 rpm in the 3rd experiment.